2022
DOI: 10.3390/ijms231810241
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Prion Inactivation by Plasma Sterilizer

Abstract: Prions, which cause transmissible spongiform encephalopathies (TSEs), are a notorious group of infectious agents with possibly the highest resistance to complete inactivation. Although various gas plasma instruments have been developed, studies on prion inactivation using gas plasma instruments are limited. Among them, the hydrogen peroxide gas plasma instrument, STERRAD® (Advanced Sterilization Products; ASP, Johnson & Johnson, Irvine, CA, USA), is recommended for prion inactivation of heat-sensitive medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Prions are more resistant to sterilization than bacterial spores. Therefore, the SAL sterility testing does not guarantee the removal of prions from treated devices [ 62 ]. The findings of Sakudo et al (2022) show that a vaporized mix of hydrogen peroxide and peracetic acid (VHPPA) inactivates prions as determined in mice infectivity assays [ 62 ].…”
Section: Current Sterilization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prions are more resistant to sterilization than bacterial spores. Therefore, the SAL sterility testing does not guarantee the removal of prions from treated devices [ 62 ]. The findings of Sakudo et al (2022) show that a vaporized mix of hydrogen peroxide and peracetic acid (VHPPA) inactivates prions as determined in mice infectivity assays [ 62 ].…”
Section: Current Sterilization Methodsmentioning
confidence: 99%
“…Therefore, the SAL sterility testing does not guarantee the removal of prions from treated devices [ 62 ]. The findings of Sakudo et al (2022) show that a vaporized mix of hydrogen peroxide and peracetic acid (VHPPA) inactivates prions as determined in mice infectivity assays [ 62 ]. Studies have demonstrated the increased efficacy of this combination of oxidizing agents as bactericidal and sporicidal solutions [ 63 ].…”
Section: Current Sterilization Methodsmentioning
confidence: 99%
“…Therefore, environmentally friendly and non-harmful disinfectants for viruses and microorganisms are still under development. Numerous types of virucidal measures, such as cold gas plasma [4], chemical disinfectants [5], 222 nm UV [6], and photocatalysis [6], have been actively studied and are reported in this collection.…”
mentioning
confidence: 99%
“…There are five generally recognized categories in the hierarchy of resistance as follows: (i) extremely resistant (prions), (ii) significantly resistant (bacterial spores, protozoan oocysts, and helminth eggs), (iii) resistant (mycobacteria, protozoan cysts, small nonenveloped viruses, and fungal spores), (iv) susceptible (vegetative bacteria, protozoa, helminths, fungi, algae, and large non-enveloped viruses), and (v) highly susceptible (enveloped viruses) [16][17][18]. Therefore, an in depth understanding of the susceptibility of microorganisms to various inactivation procedures, such as disinfection or sterilization, is necessary.…”
mentioning
confidence: 99%